Efficacy and durability of two‐ vs. three‐drug integrase inhibitor‐based regimens in virologically suppressed HIV‐infected patients: Data from real‐life ODOACRE cohort. Issue 9 (27th July 2021) - Fabbiani, Massimiliano; Rossetti, Barbara; Ciccullo, Arturo; Oreni, Letizia; Lagi, Filippo; Celani, Luigi; Colafigli, Manuela; De Vito, Andrea; Mazzitelli, Maria; Dusina, Alex; Durante, Miriam; Montagnani, Francesca; et al.
Abstract: Objectives: The aim of the present study was to compare the efficacy and durability of treatment switch to two‐drug (2DR) vs . three‐drug (3DR) integrase inhibitor (InSTI)‐based regimens in a real‐life setting. Methods: Within the ODOACRE cohort, we selected adult patients with HIV RNA < 50 copies/mL switching to an InSTI‐based 2DR or 3DR. Survival analyses were performed to estimate the probability of virological failure (VF, defined as one HIV RNA > 1000 copies/mL or two consecutive HIV RNA > 50 copies/mL) and treatment discontinuation (TD, defined as any modification, intensification or interruption of the regimen), and to evaluate their predictors. Results: Overall, 1666 patients were included, of whom 1334 (80%) were treated with a 3DR (19.9%, 25.0% and 55.1% elvitegravir‐, raltegravir‐ and dolutegravir‐based, respectively) and 332 (20%) with a 2DR (79.2% dolutegravir + lamivudine and 20.8% dolutegravir + rilpivirine). Over a median (interquartile range) follow‐up of 100 (52–150) weeks, 52 (3.1%) patients experienced VF with an incidence of 1.5/100 person‐year of follow‐up (PYFU). The estimated 96‐week probability of VF was similar for the 2DR and 3DR groups (2.3% vs . 2.8%, P = 0.53), but it was higher for elvitegravir (4.9%) and raltegravir (5.0%) than for dolutegravir (1.5%) ( P = 0.04). Four hundred (24%) patients discontinued their InSTI‐based regimen, with an incidence of 11.3/100 PYFU. At 96 weeks, 3DRs showed a higher probability of TD for any reason (20.6% vs . 11.2%, P < 0.001) and TD for toxicity (9.0% vs . 6.6%, P = 0.02) when compared with 2DRs. A higher risk of TD for central nervous system toxicity was observed for dolutegravir than for elvitegravir and raltegravir (4.0% vs . 2.5% vs . 0.6%, P = 0.005). Conclusions: In virologically suppressed HIV‐infected patients, 2DRs showed an efficacy similar to 3DRs but with better tolerability.